Revolutionize 3D-Chip Design With Open3DFlow, an Open-Source AI-Enhanced Solution - Yifei Zhu; Zhenxuan Luan; Dawei Feng; Weiwei Chen; Lei Ren; Zhangxi Tan (IEEE Open Journal of Circuits and Systems)
The escalating demand for high-performance and energy-efficient electronics has propelled 3D integrated circuits (3D ICs) as a promising solution. However, major obstacles have been the lack of specialized electronic design automation (EDA) software and standardized design flows for 3D chiplets. To bridge the gap, we introduce Open3DFlow,1 an open-source design platform for 3D ICs. It is a seven-step workflow that incorporates essential ASIC back-end processes while supporting multi-physics analysis, such as through silicon via (TSV) modeling, thermal analysis, and signal integrity (SI) evaluations. To illustrate all functionalities of Open3DFlow, we use it to implement a 3D RISC-V CPU design with a vertically stacked L2 cache on a separated die. We harden both CPU logic and 3D-cache die in a GlobalFoundries $0.18μ $ m (GF180) process with open-source PDK support. We enable face-to-face (F2F) coupling of the top and bottom die by constructing a bonding layer based on the original technology file. Open3DFlow’s open-source nature allows seamless integration of custom AI optimization algorithms. As a showcase, we leverage large language models (LLMs) to help the bonding pad placement. In addition, we apply LLM on back-end Tcl script generations to improve design productivity. We expect Open3DFlow to open up a brand-new paradigm for future 3D IC innovations.